REVITALISASI PEDAGOGI NABAWI DAN KURIKULUM KELUARGA IMRAN DALAM MENGHADAPI DEGRADASI MORAL PEREMPUAN DI ERA DIGITAL - Tasya Salsabilla; Hidayatullah Ismail; Endang Hidayati; Else Afrilia (STKIP Subang, 2026)
The advancement of digital technology has significantly transformed women's social interaction patterns, while simultaneously generating challenges in the form of moral degradation characterized by social validation culture, visual exploitation, the weakening of spiritual values, and shifts in moral orientation within digital spaces. This study aims to analyze the relevance of revitalizing Prophetic Pedagogy (Pedagogi Nabawi) and the Imran Family Curriculum in addressing women's moral degradation in the digital era. This research employs a qualitative approach using a library research method through the analysis of the Qur’an, hadith, classical Islamic exegesis (tafsir), and scholarly literature related to women’s education in Islam. The findings reveal that Prophetic Pedagogy and the Imran Family Curriculum offer an integral educational framework based on exemplary role modeling, strengthening tawhid values, character development, Islamic digital literacy, and family relationship reinforcement. Revitalization strategies are implemented through Digital Spiritual Bonding, Islamic Digital Literacy Framework, Prophetic Safe Space Education, Integrated Moral-Tech Curriculum, and Role Model Ecosystem. These models provide a relevant educational solution for developing Muslim women who are intellectually capable, morally grounded, and resilient in facing the challenges of the digital era.